A flexible UWB inverted‐F antenna for wearable application. Issue 10 (October 2017) - Xu, Li‐Jie; Wang, Hui; Chang, Yumei; Bo, Yaming
Abstract: A novel flexible antenna is proposed for communication with implanted devices in this letter. Polyimide is adopted as flexible substrate for conformal property. Based on inverted‐F structure, bow‐tie shaped structure is introduced on the top layer to achieve wideband performance. Besides, top and bottom layers are connected with a metal wall, which not only helps with miniaturization, but also leads to single‐sided fabrication requirement. Furthermore, the communication link with implanted antenna is estimated. Finally, the proposed flexible antenna is measured both in the air and around wrist in conformal form, showing good agreement with simulation results.